2016
DOI: 10.1016/j.ydbio.2016.04.021
|View full text |Cite
|
Sign up to set email alerts
|

S1pr2/Gα13 signaling regulates the migration of endocardial precursors by controlling endoderm convergence

Abstract: Formation of the heart tube requires synchronized migration of endocardial and myocardial precursors. Our previous studies indicated that in S1pr2/Gα13-deficient embryos, impaired endoderm convergence disrupted the medial migration of myocardial precursors, resulting in the formation of two myocardial populations. Here we show that endoderm convergence also regulates endocardial migration. In embryos defective for S1pr2/Gα13 signaling, endocardial precursors failed to migrate towards the midline, and the presu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…In addition, the differentiation and morphology of the anterior endoderm in ref mutants appeared intact during the stages when cardiac fusion takes place ( Figure 1—figure supplement 2E–H ). The normal appearance of the ref mutant endoderm was consistent with the unaltered progress of the endocardial precursor cells in ref mutants: endocardial cells require interactions with the anterior endoderm for their medial movement during cardiac fusion ( Holtzman et al, 2007 ; Wong et al, 2012 ; Xie et al, 2016 ), and the ref mutant endocardium seemed to reach the midline normally ( Figure 1—figure supplement 3 ). Taken together, our data suggest that defects in myocardial movement, as opposed to defects in the endoderm, cause the bifurcated cardiac morphology in ref mutants.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…In addition, the differentiation and morphology of the anterior endoderm in ref mutants appeared intact during the stages when cardiac fusion takes place ( Figure 1—figure supplement 2E–H ). The normal appearance of the ref mutant endoderm was consistent with the unaltered progress of the endocardial precursor cells in ref mutants: endocardial cells require interactions with the anterior endoderm for their medial movement during cardiac fusion ( Holtzman et al, 2007 ; Wong et al, 2012 ; Xie et al, 2016 ), and the ref mutant endocardium seemed to reach the midline normally ( Figure 1—figure supplement 3 ). Taken together, our data suggest that defects in myocardial movement, as opposed to defects in the endoderm, cause the bifurcated cardiac morphology in ref mutants.…”
Section: Resultssupporting
confidence: 59%
“…During cardiac fusion, the medial movement of the myocardium is considered to be a collective cell behavior: the cardiomyocytes travel along relatively parallel paths with very little neighbor exchange ( Holtzman et al, 2007 ) and simultaneously form intercellular junctions and create a primitive epithelial sheet ( Linask, 1992 ; Manasek, 1968 ; Stainier et al, 1993 ; Trinh and Stainier, 2004 ; Ye et al, 2015 ). Whether these coherent patterns of myocardial movement reflect active migration or passive morphogenesis is not yet resolved ( Aleksandrova et al, 2015 ; Dehaan, 1963 ; Varner and Taber, 2012 ; Xie et al, 2016 ; Ye et al, 2015 ). In either case, it is important to elucidate the specific signals that dictate the medial direction of myocardial trajectories during cardiac fusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…casanova (cas; sox32) 15 or miles apart (mil; s1pr2) (Alexander et al, 1999;Kikuchi et al, 2001;16 Kupperman et al, 2000;Ye and Lin, 2013;Yelon et al, 1999)). In cas and mil 17 mutants, both the endocardial and myocardial precursors fail to move to the 18 midline (Holtzman et al, 2007;Wong et al, 2012;Xie et al, 2016); moreover, 19 their myocardial movement defects can be detected prior to the 8 somite stage 20 (Ye et al, 2015). In contrast, the endocardial precursors seem to reach the 21 midline normally in ref mutants, and the ref myocardial movement defects 22 emerge only after the 15 somite stage.…”
Section: Cardiac Fusion 19mentioning
confidence: 99%
“…Studies tracking both endodermal and myocardial movement in chick 11 have suggested that endodermal contraction provides a physical force that pulls 12 the myocardium toward the midline (Aleksandrova et al, 2015;Cui et al, 2009;13 Varner and Taber, 2012). However, while endodermal forces may influence 14 initial phases of cardiac fusion, the observed patterns of endoderm behavior 15 seem insufficient to account for the entire path traversed by the moving 16 cardiomyocytes (Aleksandrova et al, 2015;Cui et al, 2009;Varner and Taber, 17 2012;Xie et al, 2016;Ye et al, 2015). Moreover, observations of myocardial 18 cell protrusions have suggested that these cells may actively migrate in response 19 to endodermal cues (Dehaan, 1963;Haack et al, 2014;Ye et al, 2015).…”
mentioning
confidence: 99%